Faecal incontinence in postmenopausal women with vaginal delivery history - Mik, Michał; Narbutt, Piotr; Tchórzewski, Marcin; Galbfach, Przemysław; Dziki, Adam (Menopause Review/Przegląd Menopauzalny, 2009)
Objective: Analysis of symptoms of faecal incontinence in postmenopausal women with vaginal delivery history. Evaluation of impact of comorbidities and surgery on faecal incontinence. Material and methods: The studied group comprised 39 postmenopausal women (mean age: 60.4 ±9) with faecal incontinence who were diagnosed and treated between 2003 and 2006. In the past all women had vaginal delivery. Wexner scale was used to assess faecal incontinence intensity. The function of sphincter muscles was analysed using anorectal manometry and their morphology with endorectal ultrasound (ERUS). Results: In ERUS lesion of the external sphincter was revealed in 27 women (69.2%) and lesion of the internal sphincter in a group of 22 women (61.4%). Anterior wall of the anal canal was the most common place of injury of the external and internal sphincter muscle. In a group of women who had delivered a child > 2 times symptoms of faecal incontinence were more intense than after one delivery (15.1 vs. 10.8; p < 0.05). Episiotomy had no influence on faecal incontinence in the studied group of patients. In women with bronchial asthma symptoms of faecal incontinence were significantly more intense than in the rest of the group (17.9 vs. 13.04; p < 0.05). Conclusions: The number of deliveries influences the symptoms of faecal incontinence and alters the function of sphincters. In postmenopausal women bronchial asthma intensifies the symptoms of faecal incontinence.